2022
DOI: 10.1101/2022.06.30.498242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scanning ion-conductance microscopy for studying β-amyloid aggregate formation on living cell surface

Abstract: Alzheimers disease (AD) is the most common form of dementia, a progressive neurological disorder characterized by short and long-term memory loss, including cognitive and functional impairment, which is refractory to current therapy. It is suggested that the aggregation of β-amyloid peptide on neuronal cell surface leads to various deviations of its vital function due to myriad pathways defined by internalization of calcium ions, apoptosis promotion, reduction of membrane potential, synaptic activity loss etc.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Their findings revealed that cell surface roughness is unevenly distributed, with the plasma membrane above the nucleus being the smoothest. 130 Leitao et al developed a high-speed SICM based on highbandwidth large-scale piezo actuator able to perform timeresolved, long-term topographical mapping of living eukaryotic cells. 131 They demonstrated continuous surface topography measurement of large areas (80 μm × 80 μm) with good spatial resolution (512 × 512 pixels) and temporal resolution (from 0.5 s/frame to 20 min/frame depending on scan area).…”
Section: Conductance Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings revealed that cell surface roughness is unevenly distributed, with the plasma membrane above the nucleus being the smoothest. 130 Leitao et al developed a high-speed SICM based on highbandwidth large-scale piezo actuator able to perform timeresolved, long-term topographical mapping of living eukaryotic cells. 131 They demonstrated continuous surface topography measurement of large areas (80 μm × 80 μm) with good spatial resolution (512 × 512 pixels) and temporal resolution (from 0.5 s/frame to 20 min/frame depending on scan area).…”
Section: Conductance Microscopymentioning
confidence: 99%
“…Gesper used SICM and fluorescence correlation spectroscopy to assess diffusion in cell membranes. Their findings revealed that cell surface roughness is unevenly distributed, with the plasma membrane above the nucleus being the smoothest …”
Section: High-throughput Scanning Ion Conductance Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Such modifications constitute a long list including but not limited to: phosphorylation, isomerisation, citrullination, pyroglutamylation, and covalent cross-linking. Post-translational modifications affect the process of Aβ aggregation, change the structure and the biological effects of the oligomers [ 121 ], and influence Aβ hydrolysis by the angiotensin-converting enzyme thereby promoting its accumulation [ 122 ]. For example, it was shown that isomerisation of the aspartate residue in the seventh position accelerated the development of amyloidosis in vivo [ 67 ] and enhanced the toxic properties of the peptide [ 123 ].…”
Section: Factors Behind the Different Properties Of Brain-derived Cel...mentioning
confidence: 99%